Design and testing of breathing retraining device a multiphasic exploratory study in healthy subjects - Devmurari, Parthkumar; Rathod, Priyanshu; Patel, Chetan; Parmar, Khushboo (European journal of clinical and experimental medicine, 2025)
Introduction and aim. Traditional spirometers are limited by bulkiness and lack of biofeedback, which can hinder their effec tiveness in pulmonary rehabilitation. This study aimed to evaluate the accuracy of an innovative breathing retraining device in measuring inhaled volume and assess user satisfaction compared to standard spirometers. Material and methods. A multiphasic exploratory study was conducted with 102 healthy adults (aged 18–60 years). The study included three phases: need analysis through focus group discussions, prototype development using polycarbonate materials and 3D printing, and effectiveness testing. Inhalation exercises were performed with both the new device and a standard spi rometer. Primary outcomes were inhaled volume and marker displacement, with user satisfaction assessed via the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST 2.0) questionnaire. Results. The new device showed a strong correlation between inhaled volume and marker displacement (r=0.842, p<0.001). The mean inhaled volume was 2.07±0.61 liters, with a mean marker displacement of 5.19±0.59 cm. The mean QUEST 2.0 satis faction score was 3.54, indicating high user satisfaction. Conclusion. The redesigned breathing retraining device not only addresses critical gaps in existing technologies but also offers a practical, user-friendly solution for pulmonary rehabilitation. By combining accuracy, real-time feedback, and portability, this innovation has the potential to redefine respiratory therapy standards in both clinical and home-based settings, paving the way for broader applications and improved patient outcomes.